WATCH THIS SPACE - Vaughan, Cathy (PINS-Psychology in Society, 2025)
Simon, B (2004) Identity in modern society: A social psychological perspective. Oxford: Blackwell Publishing. ISBN 0-631-22747-4 pbk. Pages xvii + 222.